THE CRIMES OF THE NATIONS IN AMOS 1-2 - R Kessler (Acta Theologica)
In the oracles against the nations in Amos 1-2, several acts of the nations are condemned as “transgressions” or “crimes”. The text mentions “threshing” one’s enemy, deportations and slave trade, acting in wrath and anger, expanding one’s territory by conquest, ripping open pregnant women, and desecrating corpses. Although these are clearly acts of violence, they are viewed as legitimate in some contexts. Gods and kings are practising them. It depends on the perspective. The author of Amos 1-2 sides with the victims and identifies the perspective of the victims with God’s perspective. This lays solid ground for the Book of Amos, in which the social violence of the powerful against the weak and vulnerable in Israelite society is judged in the same way as a crime against God.